The Charachter of Lieutenant Ogarkov: Confusion or Fault (the Lesson-research of E. Kazakevich's Story "Two in steppe") (Филологический класс, 2010)
Working out of a lesson-seminar of E.Kazakevich's story «two in steppe» (1948) is offered in the article. The problem of the author's relation to the hero who has not executed the military order in one of the most dramatic of the periods of the Great Patriotic War is in the lesson center. Reflections over hero's charachter and a position of the author are entered in conversation about social-political situations in the country after the Great Patriotic War. Authors offer problem questions and tasks for the group and face-to-face work, focusing on the text analysis («the dialectician of soul» the protagonist, system of characters, etc.) and discussion of debatable questions.